Mini-Review: Nod Factor Regulation of Phytohormone Signaling and Homeostasis During Rhizobia-Legume Symbiosis - Buhian, William P.; Bensmihen, Sandra (Frontiers in Plant Science, 2018)
The rhizobia-legume symbiosis is a mutualistic association in which bacteria provide plants with nitrogen compounds and the plant provides bacteria with carbon sources. A successful symbiotic interaction relies on a molecular dialog between the plant and the bacteria, and generally involves rhizobial lipo-chitooligosaccharide signals called Nod factors (NFs). In most cases, specific NF perception is required for rhizobia to enter root cells through newly formed intracellular structures called infection threads (ITs). Concomitantly to IT formation in root hairs, root cortical cells start to divide to create a new root organ called the nodule, which will provide the bacteria with a specific micro-environment required for symbiotic nitrogen fixation. During all these steps of plant–bacteria interaction, new plant cellular compartments and developmental programs are activated. This interaction is costly for the plant that tightly controls symbiosis establishment and functioning. Phytohormones are key regulators of cellular and developmental plasticity in plants, and they are influential endogenous signals that rapidly control plant responses. Although early symbiotic responses were known for decades to be linked to phytohormone-related responses, new data reveal the molecular mechanisms involved and links between phytohormones and the control of early symbiotic events. Reciprocally, NF signaling also targets phytohormone signaling pathways. In this review, we will focus on the emerging notion of NF and phytohormone signaling crosstalk, and how it could contribute to the tight control of symbiosis establishment in legume host plants.